PERBEDAAN KADAR IL-6 PADA HUVECs NORMAL DENGAN HUVECs NORMAL YANG DIPAPAR PLASMA HAMIL PENDERITA PREEKLAMPSIA - Rahayu, Budi; Nurdiana; Windu Baktiyani, Siti Candra (Universitas Jenderal Achmad Yani Yogyakarta, 2015)
Background : Preeclampsia is a condition where the blood pressure is increasing (≥140/90 mmHg) followed by proteinuria (≥300 mg/24 hour or ≥1+ in stick test) in pregnant women after 20 weeks of pregnancy. Released placenta factor cause the damage in endothelial cells which lead to the excessive increase on pro inflammation factor interleukin 6 (IL-6). Objective: This study aimed to investigate whether level IL-6 on normal HUVECs with normal HUVECs induced by plasma from preeclamptic patients. Research Method: True experimental research using posttest only control group approach, conducted in the laboratory with invitro. HUVECs culture was divided into 5, that were normal HUVECs without treatment (K-); HUVECs preeclampsia model (K+). Measurement on the levels of IL-6 used ELISA (Enzyme-Linked Immunosorbent Assay). Result: Independent sample t-test showed that there were significant differences (p=0.000<α) on the average of IL-6 levels between the negative control group (1.64±0.12 pg/ml) and the positive control group (31.64±11.69 pg/ml). Conclusion: Adding the patient’s preeclampsia plasma into normal HUVECs can increase levels of IL-6. Keyword: Patient’s preeclampsia plasma, HUVECs, and IL-6.